2012
DOI: 10.1177/1753425912459975
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 activation efficiency by high or low molecular mass poly I:C

Abstract: Toll-like receptor 3 (TLR3) plays a critical role in initiating type I IFN-mediated innate immunity against viral infections. TLR3 recognizes various forms of double stranded (ds) RNA, including viral dsRNA and a synthetic mimic of dsRNA, poly I:C, which has been used extensively as a TLR3 ligand to induce antiviral immunity. The activation efficiency of TLR3 by poly I:C is influenced by various factors, including size of the ligands, delivery methods and cell types. In this study, we examined the stimulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 34 publications
(69 reference statements)
2
69
1
Order By: Relevance
“…2B). In contrast with a previous report on the efficacy of TLR3 activation by HMW-poly I:C, which was significantly higher than that by TLR3 (LMW) [17], prominent differences were not observed between TLR3 and TLR3 (LMW) in T-MSCs in CCR6 expression.…”
Section: Chemokine Receptor Expression In T-mscs After Tlr Stimulationcontrasting
confidence: 85%
“…2B). In contrast with a previous report on the efficacy of TLR3 activation by HMW-poly I:C, which was significantly higher than that by TLR3 (LMW) [17], prominent differences were not observed between TLR3 and TLR3 (LMW) in T-MSCs in CCR6 expression.…”
Section: Chemokine Receptor Expression In T-mscs After Tlr Stimulationcontrasting
confidence: 85%
“…It is known that TLR3, RIG-I, and MDA5 recognize the dsRNA analog polyI:C differently depending on its length (Kato et al, 2008;de Rivero Vaccari et al, 2012;Zhou et al, 2013). We have recently shown that TLR3, RIG-I, and MDA5 are up-regulated in astrocytes when activated with polyI:C, which may behave like a long dsRNA under our experimental conditions (Ibi et al, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…Notably, several commercial formulations of poly(I:C) exist with potentially different effects on immune cells (56,57). The availability of various formulations of poly(I:C) may be advantageous, because its molecular size and chemical modifications play an important fine-tuning role in stimulating innate cell responses and may allow for a greater versatility in different pathologic conditions.…”
Section: Discussionmentioning
confidence: 99%